REALIZATION OF THE EXPERIENTIAL FUNCTION IN WRITING REPORT TEXT AT SECOND-GRADE STUDENTS OF SMA BUDDHIS BODHICITTA MEDAN - Lubis, Rointan; Pakpahan , Carolina; Siahaan, Sahat Taruli (English Language Teaching Prima Journal (ELT), 2024)
The purpose of this study was to find out how is the experiential function realized in the report text writing of students in the second grade at SMA Buddhis Bodhicitta Meda, and what is the most dominant process found in the report text writing of students in the second grade at SMA Buddhist Bodhicitta Medan. This study used a qualitative descriptive method in analyzing data. Data was taken from the writings of 33 students as data. The data used is 486 clauses consisting of 6 processes which are experiential functions. From the data obtained, material processes were obtained 246 times (50.6%), mental processes 22 times (4.5%), relational processes 22 times (41.8%), behavioral processes 1 time (0.2%), verbal process 5 times (1%), and the last is existential process 9 times (1.9%). In this study, material processes were the most widely found or predominantly experiential function process type used by students in their report text writing. The realization of such a process of experiential functioning is most widely used by students because the error use of chosen verb in report text writing based on the lexicogrammatical features. Each student uses the process of such an experiential function to indicate something that depends on the intent to be conveyed. This type of process experiential function is used to describe an ongoing event by using action verbs in its description according to the social function of the report text.